A 10-year analysis of the Bronco fitness test in male and female Super Rugby athletes: the effect of sex and positional group - Weakley, J.; Murphy, S.; Kan, M.; Thurlow, F.; Mitchell, L.; Whelan, B.; Williams, P.; King, A. J.; Read, D. B. (The Journal of Strength and Conditioning Research, 2026)
The Bronco fitness test is a commonly used assessment of high-intensity running capacity. This study aimed to (a) analyze 10 years of Bronco fitness testing data from male and female Super Rugby athletes by sex and positional group and (b) develop practical percentile thresholds. Bronco test data were retrospectively analyzed from 462 elite rugby athletes (303 males, 159 females), totaling 1,668 observations. Athletes were grouped by sex and positional groups. Linear mixed-effects models were used to assess differences, with Cohen's d effect sizes calculated. Percentile thresholds were derived from model outputs. Male athletes completed the Bronco significantly faster than female athletes (5:11 ± 00:02 vs. 6:19 ± 00:03 minutes:secs; p < 0.001; d = 1.78). Backs outperformed forwards in both sexes (male: 4:57 ± 00:02 vs. 5:21 ± 00:02; d = 1.09; female: 5:52 ± 00:06 vs. 6:38 ± 00:05; d = 0.98). Among male athletes, halves were the fastest positional group, while the Back 3 was fastest among female athletes. Front rowers consistently recorded the slowest times. Greater performance variability was observed in the female cohort, potentially reflecting the continued development of the female game. These findings provide normative data and percentile thresholds to guide profiling, conditioning, and long-term athlete development. Practitioners are encouraged to use these benchmarks to inform position-specific training and performance targets. The percentile tables and positional benchmarks presented can support practitioners and sport scientists in evaluating high-intensity running capacity, setting development goals, and tailoring conditioning programs for male and female Super Rugby athletes.